2021
DOI: 10.1017/s0144686x20001841
|View full text |Cite
|
Sign up to set email alerts
|

Access to health care among racialised immigrants to Canada in later life: a theoretical and empirical synthesis

Abstract: Evidence that immigrants tend to be underserved by the health-care system in the hosting country is well documented. While the impacts of im/migration on health-care utilisation patterns have been addressed to some extent in the existing literature, the conventional approach tends to homogenise the experience of racialised and White immigrants, and the intersecting power axes of racialisation, immigration and old age have been largely overlooked. This paper aims to consolidate three macro theories of health/be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 120 publications
(170 reference statements)
2
42
0
Order By: Relevance
“…These findings also echoed a recent provincial study in British Colombia, which found that females, those with less than high school education, racialized and indigenous groups had lower intentions to receive a COVID-19 vaccine [29]. Barriers to accessing health care, including lower vaccine uptake for infectious disease prevention, have been frequently documented among migrants [15,25] racialized populations [61,62] and socioeconomically disadvantaged groups [63], who are fundamentally deprived of health-promoting resources and at more risk of COVID-19 infection and adverse clinical outcomes [64]. In addition, this research demonstrates that health risk perceptions about seeing a doctor were more prominent in the im/migrant community, regardless of a publicly funded health care system in Canada.…”
Section: Main Findings and Implications For Health Practicesupporting
confidence: 63%
See 3 more Smart Citations
“…These findings also echoed a recent provincial study in British Colombia, which found that females, those with less than high school education, racialized and indigenous groups had lower intentions to receive a COVID-19 vaccine [29]. Barriers to accessing health care, including lower vaccine uptake for infectious disease prevention, have been frequently documented among migrants [15,25] racialized populations [61,62] and socioeconomically disadvantaged groups [63], who are fundamentally deprived of health-promoting resources and at more risk of COVID-19 infection and adverse clinical outcomes [64]. In addition, this research demonstrates that health risk perceptions about seeing a doctor were more prominent in the im/migrant community, regardless of a publicly funded health care system in Canada.…”
Section: Main Findings and Implications For Health Practicesupporting
confidence: 63%
“…In addition, this research demonstrates that health risk perceptions about seeing a doctor were more prominent in the im/migrant community, regardless of a publicly funded health care system in Canada. This is another worrying situation for im/migrants that could lead to underutilization of needed health services (e.g., delay of diagnostic tests and specialized care) in the host country during turbulence times [15,65]. Thus, building COVID-19 vaccine confidence among these underserved populations primarily relies on the public health systems to become more accessible and sensitive on a structural basis, rather than placing the personal responsibility on these equity-seeking groups to become less hesitant [8].…”
Section: Main Findings and Implications For Health Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Grounded in the socioecological paradigm ( Davison et al., 2021 ; Kawachi et al., 2002 ; Lin, 2021 ) and the social determinants of health framework ( Marmot, 2005 ) and fundamental social cause theory ( Phelan and Link, 2005 ; Phelan et al., 2010 ), the present study hypothesizes that individuals who are affected by the disruptions from the COVID-19 pandemic at macro-, meso‑ and micro-levels of their ecosystems may be more susceptible to adverse mental health consequences (see Fig. 1 for the conceptual framework).…”
Section: Introductionmentioning
confidence: 98%